EDUCAÇÃO AMBIENTAL NO USO E DESCARTE DE PILHAS E BATERIAS - Brum, Zélio Rumpel; Silveira, Djalma Dias da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This study aimed to promote awareness of people to the fact of the necessity ofenvironmental care for the proper use and disposal of batteries. The first step was theawareness, that occurred by the survey data, which questions regarding batteries withsubsequent delivery of a booklet and lecture on law and harm caused by waste batteries.In a second step, we performed selective collection of batteries. The main results of thesurvey data indicated that 80% of answers rarely discard batteries, but when it does, usethe trash for disposal. We also observed that 46% of respondents said they did not knowof the problems that contamination by products such as mercury, copper and lead cancause to human health. Answers understand that the responsibility of the correctdestination of these materials is the population itself, ignoring the law that indicatesmanufacturing companies as the main responsible for the collection. This work is expectedto arouse the civility, sensitivity, and adoption of new habits on the planet where we live.